Formação de professoras normalistas rurais nas escolas técnicas federais brasileiras (1954-1963) - Visquetti, Carminha Aparecida (2023)
ABSTRACT: This thesis investigated the training of rural female teachers in Brazilian federal technical schools. The general objective was to historicize and analyze how the training of rural female teachers in the Rural Home Economics Teaching Course, at the secondary level, took place in Brazilian federal technical schools, from 1954 to 1963. The specific objectives were: a) to analyze how the training of rural teachers in Mexico influenced the training of rural teachers in Brazil; b) to map the federal technical schools that offered the Teaching Course in Rural Home Economics; c) to investigate the subjects and some school practices of this training course in federal technical schools. The time frame begins in 1954, when these courses were implemented in Brazil's federal technical schools under the guidance of the Superintendence of Agricultural Education (SEAV), and ends in 1963, when the classes that began in 1962 graduated and these courses were no longer offered due to the provisions of the 1961 Law on the Guidelines and Bases of National Education (LDB). The sources of research were: regulations and legislation for the Rural Normal Course in Teaching Rural Home Economics; issues of the periodicals Revista Brasileira de Estudos Pedagógicos - RBEP and Revistas da Campanha Nacional de Educação Rural - RCNER, and school textbooks. After reading and analyzing the sources, I established the following categories of analysis: Training of rural teachers, Rural Normal Course and Rural Home Economics Teaching Course at federal technical schools. The research problem was: how was the training of rural normalists in the Rural Home Economics Course at Brazilian federal technical schools shaped? The methodology for analyzing the sources was supported by authors of the New History, such as Marc Bloch (2002) and Jacques Le Goff (1990), who warned of the need to break with writing that only considers official records, based on a single point of view. Training for the rural normal teaching profession in Brazil was addressed by Nilce Vieira Campos Ferreira (2012, 2014) and Manoel Bergström Lourenço Filho (1952, 2004), who provided contributions on the training of rural teachers in Brazil. Theorists such as Alicia Civera (2003, 2006, 2010, 2013) and Oresta López Pérez (2006, 2020) made important contributions to the training of Mexican rural teachers. The results of the research showed that the Brazilian Rural Normal Course offered at Brazilian federal technical schools between 1954 and 1963 provided the first access for women to federal technical schools, since until that time these institutions offered technical courses aimed only at male students, such as Agrotechnical Courses, Agriculture, Agricultural Mechanics, among others. The thesis confirmed that the training of rural teachers in technical schools did not focus on specific pedagogical training, but divided the subjects into General Culture, which included Portuguese; Mathematics; Natural Sciences and Technical Culture, concentrating the greatest workload in the subjects of: Sanitary Education, Hygiene; Dietetics; Dietetics; Orphic Singing; Home Economics, Food Theory; Culinary Art; Manual Work and Drawing. Only one subject in the course was intended for teacher training: General Methodology. Therefore, training for rural teaching was not the main objective of the course. In reality, rural teachers were trained with varied knowledge about the countryside and, above all, knowledge about household chores. Furthermore, it is noted that an insignificant number of teachers were trained in federal technical schools, given the need to train teachers to work in the rural areas of the country during the period studied.